Evaluation of the Containment of Antimicrobial-Resistant Salmonella Species from a Hazard Analysis and Critical Control Point (HACCP) and a Non-HACCP Pig Slaughterhouses in Northeast Thailand - Xin Wu; Fanan Suksawat; Allen L. Richards; Seangphed Phommachanh; Dusadee Phongaran; Sunpetch Angkititrakul (Pathogens, 2019)
To evaluate the containment of antimicrobial-resistant (AMR) Salmonella contaminations of a HACCP slaughterhouse (HACCP SH) and a non-HACCP slaughterhouse (non-HACCPSH), 360 paired pig rectal (representing the farm pig status) and carcass samples (representing the contamination) were collected equally from the two slaughterhouses that serviced 6 and 12 farms, respectively, in Northeast Thailand (n = 720). The purified Salmonella isolates were serotype identified, antimicrobial susceptibility tested, and pulsed-field gel electrophoresis (PFGE) assessed. Four evaluations of two slaughterhouses were examined: (1) the means of slaughtering contamination rates (SCR) (to evaluate the contamination level by averaged farm SCRs): the HACCP SH decreased contamination (SCR: −48.89% ± 8.80%, n = 6), whereas the non-HACCP SH increased (SCR: 14.31% ± 9.35%, n = 12). (2) The serotype diversity: the HACCP SH decreased the diversity from the rectal group (110 isolates, 9 serotypes) to carcass group (23 isolates, 3 serotypes), whereas there was no decrease in the non-HACCP SH (rectal group (66 isolates, 14 serotypes) and carcass group (31 isolates, 10 serotypes)). (3) The AMR patterns: the HACCP SH decreased from rectal group (96 isolates, 7 patterns) to carcass group (22 isolates, 1 pattern), whereas there was no decrease from the non-HACCP SH rectal group (22 isolates, 7 patterns) to carcass group (48 isolates, 8 patterns). (4) The estimated indirect contamination rate (by serotype screening and PFGE confirmation): the HACCP SH was 60.87% (14/23), whereas the non-HACCP SH was 98.48% (65/66). This study indicates that both the slaughterhouses keep a high level of indirect contamination; the HACCP SH decreases Salmonella contaminations and reduces the AMR patterns, the non-HACCP SH increases contaminations.